Peran Media Gambar dalam Meningkatkan Pemahaman Siswa terhadap Materi IPA di Sekolah Dasar - Nadila Putri Lestari; Ari Suriani (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This article aims to examine the role of visual media in enhancing elementary school students’ understanding of science (IPA) concepts through a literature review approach. The study was conducted by analyzing various references, including academic journals, instructional books, and educational articles related to the topic. The findings indicate that visual media plays a significant role in helping students comprehend abstract scientific concepts by presenting information in an engaging and visually accessible manner. Furthermore, visual media has been shown to increase students’ learning motivation and participation in the learning process. Therefore, the use of visual media is recommended as an effective instructional tool in elementary science education.